Penerapan Manajemen Kurikulum Berbasis Penguatan Pendidikan Karakter untuk Meningkatkan Mutu Pembelajaran di SMP Negeri 1 Pamatang Silimahuta - Nainggolan, Lia Erika; Saragih, Hisarma; Nainggolan, Pinondang; Damanik, Sarintan E.; Purba, Tioner (Indo-MathEdu Intellectuals Journal, 2025)
The character education-based curriculum is an approach to the curriculum designed to integrate character values into the entire learning process, both through subjects, extracurricular activities, and the culture at SMP Negeri 1 Pamatang Silimahuta. This study aims to evaluate the planning, implementation, and management constraints of the character strength-based curriculum at SMP Negeri 1 Pamatang Silimahuta using qualitative methods. Data was collected through interviews, observations, and documentation with subjects including the Principal, Deputy Principal of Curriculum, Teachers, and Students. The research results show that the character-strengthening based curriculum management at SMP Negeri 1 Pamatang Silimahuta is implemented inclusively involving school stakeholders and parents. This curriculum is considered effective in addressing the challenges of character education and supporting project-based learning. The active participation of stakeholders supports the improvement of learning quality. Its implementation shows positive results, although it faces challenges such as external influences and the use of gadgets. Evaluation through observation indicates a great hope from all parties for this curriculum to continue to be developed in accordance with the demands of the times.